ECLECTIC SYSTEM OF INFORMATION FILTERING BASED ON COMPUTING INTELLIGENCE FOR RECOMMENDATION OF COLOMBIAN CARIBBEAN TOURIST ATTRACTIONS - Tovar Garrido, Luis C.
Recommendation systems can help people find items that best suit their tastes and needs when overwhelmed with information overload. These systems have been used in different domains such as music and movies, but have also proven to beuseful in the field of tourist attractions. This article presents an eclectic information filtering system for tourist attractions in the caribbean region of Colombia. The proposed solution suggests tourist attractions of interest to a user based on their rating profile, preferences and personal tastes.The system adopts a eclectic approach, combining three different recommenders in order to find themost optimal algorithm for this complex domain. All this was oriented to a mobile application and evaluated by a group of test users. The results showed the usefulness of recommendation systems for the tourism domain allowing to generate tourist visits adapted to the profile of the user, simplifying the task of planning a trip.